Study of graphical authentication system based on persuasive rotation, resizing and cued click point (GUAS) - Zolkipli, Mohamad Fadli (2014)
Nowadays, the most accepted computer authentication technique is to use alphanumerical usernames with text-based password. This method has been proven to have significant multiple weaknesses. For example, users tend to choose the passwords that can be easily cracked. On the other hand, if a password is difficult to guess, then it is often hard to memorize. To address those issues, some researchers have developed graphical-based authentication algorithm that implement pictures as passwords. In this project, I had conduct an in-depth comprehensive review regarding the existing graphical password scheme. Furthermore, I classify these existing Graphical User Authentication System (GUAS) into two kinds of mechanism, which are: recognition-based and recall-based approaches. Besides that, I will examine the strengths and limitations of each technique and identify the future research directions. I also developed an improved version of GUAS algorithm address the common limitation exists in the current graphical password techniques. Overall, in this thesis, the scheme of the new technique will be proposed, the advantages of technique will be outlined and lastly, the future work will be anticipated as well